Surface effects on moving vortices in superconducting stripes - Reis, J. D.; Venegas, Pablo Antonio [UNESP]; Mello, Denise Fernandes de [UNESP]; Cabrera, G. G. (Elsevier B.V., 2007)
Size and surface dynamical effects are investigated in thin superconducting stripes with variable width. We perform numerical simulations of the vortex dynamics, with the inclusion of the surface confining potential and a random distribution of pinning centers. To fully characterize the vortex flow, we calculate the differential resistance, the transverse diffusion coefficient, the structure factor and the intensity of the Bragg peaks, as functions of the transport force. We found that surface effects induce a premature ordering of the flux line lattice, and the system displays plastic and smectic behavior only in a very narrow range of forces. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: superconductivity; vortex dynamics; surface effects